If secA-tanA=x then prove that 1/x=secA+tanA
Answers
Answered by
2
We know that,
sec²A - tan²A = 1
or, (secA - tanA) (secA + tanA) = 1
or, x (secA + tanA) = 1
or, 1/x = secA + tanA
Therefore, 1/x = secA + tanA (Proved)
#
sunilchauhan97p5etkt:
Okay and Thank you so much
Answered by
2
Heya, As you have seen a method [above] ,
I have a new,
××××××××××××××××××××÷÷×××÷
x = SecA - tanA
Then,
![\frac{1}{x} = \frac{1}{ \sec(A) - \tan(A) } \frac{1}{x} = \frac{1}{ \sec(A) - \tan(A) }](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Bx%7D+%3D+%5Cfrac%7B1%7D%7B+%5Csec%28A%29+-+%5Ctan%28A%29+%7D+)
By rationalization,
![\frac{1}{x} = \frac{1}{ \sec(A) - \tan(A) } \times \frac{ \sec(A) + \tan(A) }{ \sec(A) + \tan(A) } \\ \\ \frac{1}{x} = \frac{ \sec(A) + \tan(A) }{ { \sec(A) }^{2} - { \tan(A) }^{2} } \frac{1}{x} = \frac{1}{ \sec(A) - \tan(A) } \times \frac{ \sec(A) + \tan(A) }{ \sec(A) + \tan(A) } \\ \\ \frac{1}{x} = \frac{ \sec(A) + \tan(A) }{ { \sec(A) }^{2} - { \tan(A) }^{2} }](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Bx%7D+%3D+%5Cfrac%7B1%7D%7B+%5Csec%28A%29+-+%5Ctan%28A%29+%7D+%5Ctimes+%5Cfrac%7B+%5Csec%28A%29+%2B+%5Ctan%28A%29+%7D%7B+%5Csec%28A%29+%2B+%5Ctan%28A%29+%7D+%5C%5C+%5C%5C+%5Cfrac%7B1%7D%7Bx%7D+%3D+%5Cfrac%7B+%5Csec%28A%29+%2B+%5Ctan%28A%29+%7D%7B+%7B+%5Csec%28A%29+%7D%5E%7B2%7D+-+%7B+%5Ctan%28A%29+%7D%5E%7B2%7D+%7D+)
We know, sec²∅-tan²∅ = 1
Then,
![\frac{1}{ x } = \frac{ \sec(A) + \tan(A) }{1} \frac{1}{ x } = \frac{ \sec(A) + \tan(A) }{1}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B+x+%7D+%3D+%5Cfrac%7B+%5Csec%28A%29+%2B+%5Ctan%28A%29+%7D%7B1%7D+)
1/x = SecA + tanA
Hence, proved
I hope this will help you
(-:
I have a new,
××××××××××××××××××××÷÷×××÷
x = SecA - tanA
Then,
By rationalization,
We know, sec²∅-tan²∅ = 1
Then,
1/x = SecA + tanA
Hence, proved
I hope this will help you
(-:
Similar questions